Dysphagia Outcomes Following Surgical Management of Unilateral Vocal Fold Immobility: A Systematic Review and Meta‐analysis. (28th December 2022) - Coulter, Michael; Marvin, Kastley; Brigger, Matthew; Johnson, Christopher M.
Abstract: Objective: To assess dysphagia outcomes following surgical management of unilateral vocal fold immobility (UVFI) in adults. Data Sources: Ovid MEDLINE, Embase, Web of Science, and Cochrane Central. Review Methods: A structured literature search was utilized, and a 2‐researcher systematic review was performed following PRISMA guidelines. Extractable data were pooled, and a quantitative analysis was performed with a random effects model to analyze treatment outcome and complications by procedure. Results: A total of 416 publications were screened and 26 met inclusion criteria. Subjects encompassed 959 patients with UVFI who underwent 916 procedures (n = 547, injection laryngoplasty; n = 357, laryngeal framework surgery; n = 12, laryngeal reinnervation). An overall 615 were identified as having dysphagia as a result of UVFI and had individually extractable outcome data, which served as the basis for a quantitative meta‐analysis. In general, dysphagia outcomes after all medialization procedures were strongly positive. Quantitative analysis demonstrated a success rate estimate of 90% (95% CI, 75%–100%) for injection laryngoplasty and 92% (95% CI, 87%–97%) for laryngeal framework surgery. The estimated complication rate was 7% (95% CI, 2%–13%) for injection laryngoplasty and 15% (95% CI, 10%–20%) for laryngeal framework surgery, with minor complications predominating. Although laryngeal reinnervation could not be assessed quantitatively due to low numbers, qualitative analysis demonstrated consistent benefit for a majority of patients for each procedure. Conclusion: Dysphagia due to UVFI can be improved in a majority of patients with surgical procedures intended to improve glottal competence, with a low risk of complications. Injection laryngoplasty and laryngeal framework surgery appear to be efficacious and safe, and laryngeal reinnervation may be a promising new option for select patients.